Modeling learners' behavioral intention toward using artificial intelligence in education - Noel Nino Valle; Ronnel Victor Kilat; Joshlen Lim; Edralin General; Jacquiline Dela Cruz; Sarah Jane Colina; Ivy Batican; Lislee Valle (Social Sciences and Humanities Open)
Artificial Intelligence (AI) transforms several dimensions of society and industry. However, the rapid advancements in AI technology present both opportunities and challenges for education. This paper investigated the factors that affect learners' behavioral intention toward using artificial intelligence. The proposed model was tested using partial least square-structural equation modeling (PLS-SEM) on a self-reported survey of 886 junior high school to college learners in Cebu, Philippines. Results showed that 5 out of 9 hypothesized paths are significant. Results revealed that social influence and perceived knowledge of using AI are significant predictors of attitude toward using AI, and only three have a significant effect on behavioral intention: performance expectancy, perceived knowledge of using AI, and attitude towards using AI. These findings suggest that the people around them and their knowledge of AI tools affect learners' attitudes toward using AI. Learners intend to use AI because they believe that AI will help improve their work, they have the knowledge of using AI, and they have a positive attitude towards using AI.